Supporting water-food-land nexus policy coherence through integrated agrifood advisory and extension system in Egypt - Eldabbagh, Fayrouz; Brouziyne, Youssef (EDP Sciences, 2024)
Building policy coherence is significant in governing natural resources, especially in a changing climate and growing population. Designing and implementing coherent climate-adaptive water productivity policies through holistic and integrated knowledge could manage the growing demand for food and water, and sustain small-scale farmers' livelihoods and economies, which is the aim of this research. This study focuses on the analysis of power dynamics and the social network that evolves around the control of information and technical assistance that shape policy narratives. Results showed that donors and financial institutions are the primary powers to control and organize knowledge and technical assistance linked to soil-water conservation especially when it’s combined with mobilizing relevant funds. Many smallholder farmers still adopt traditional patterns of cultivation due to the siloed knowledge gaps in the extension services of governmental entities, the unreachability of extension services, the lack of trust in their guidance, and the absence of innovations’ scalability. Building integrated extension services between ministries, by providing equal and suitable financial packages. This would be feasible by managing the coordination with financial institutions, monetary and nonmonetary incentives, and building on existing farmers’ collective organizations and farmers’ pioneers to enable a sociological transition to water productivity.